Roadside hawk (Rupornis magnirostris) hit by an oncoming vehicle while capturing a striped snake (Lygophis anomalus) - Lyons, Sebastián (2022)
One of the most apparent origins of biodiversity loss caused by humans is infrastructural development of roads. Yet they offer certain benefits for some animals, such as hunting opportunities with lower energy costs and consumption of carrion earlier hit by vehicles. Raptors find roads a particularly favorable environment, perching on poles or overhead cables and waiting to attack their prey as it crosses a road. This paper describes the first ever recorded predation by a roadside hawk (Rupornis magnirostris) of a striped snake (Lygophis anomalus) supportable by material evidence, when both the raptor and the snake were hit by a vehicle immediately after the snake was caught. The study contributes to knowledge about the roadside hawk’s diet and illuminates the problem these human infrastructures pose for animals. Future research on roads birds of prey use as hunting sites could contribute toward improvements in conservation programs for birds of prey species.